A thymidylate synthase polymorphism is associated with increased risk for bone toxicity among children treated for acute lymphoblastic leukemia. Issue 7 (13th December 2016) - Finkelstein, Yaron; Blonquist, Traci M.; Vijayanathan, Veena; Stevenson, Kristen E.; Neuberg, Donna S.; Silverman, Lewis B.; Vrooman, Lynda M.; Sallan, Stephen E.; Cole, Peter D.
Abstract: Background: Bone fractures and osteonecrosis frequently complicate therapy for childhood acute lymphoblastic leukemia (ALL). Bone toxicity has been associated with exposure to corticosteroids and methotrexate (MTX) and age greater than 10 years. We tested whether common genetic polymorphisms were associated with bone toxicity during treatment for ALL. Procedure: A total of 615 of 794 children enrolled on Dana Farber Cancer Institute ALL Consortium protocol 05‐001 (NCT00400946) met eligibility criteria for inclusion in this analysis. Nineteen candidate polymorphisms were selected a priori, targeting genes related to glucocorticoid metabolism, oxidative damage, and folate physiology. Polymorphisms were genotyped using either PCR‐based allelic discrimination or PCR product length analysis. Results: Twenty percent of subjects were homozygous for two 28 bp repeats (2R/2R, where 2R is two 28‐nucleotide repeats within the 5' untranslated region [UTR] of the thymidylate synthase [TS] gene) within the 5′ UTR of the gene for TS. This 2R/2R genotype was associated with increased risk of osteonecrosis among children younger than 10 years at diagnosis (multivariable hazard ratio [HR] 2.71; 95% confidence interval [CI] 1.23–5.95; P = 0.013), and with bone fracture among children ≥ 10 years (multivariable HR 2.10; 95% CI 1.11–3.96; P = 0.022). No significant association was observed between TS genotype and red blood cell (RBC) folate, RBC MTX, or relapse risk. Conclusions: A common genetic variant is associated with increased risk of osteonecrosis among children younger than 10 years at diagnosis and with bone fractures among older children. These findings suggest that children and adolescents with the 2R/2R TS genotype should be closely monitored for the development of bone toxicity during therapy for ALL, and support a clinical trial testing the efficacy of protective interventions specifically in this vulnerable population.